Porozumienia integracyjne w kontenerowej żegludze morskiej. Geneza, rozwój i stan obecny w kontekście obowiązujących przepisów Unii Europejskiej - Bartosiewicz, Aleksandra (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
Common maritime transport policy in Europe was developed only in the mid 70-ties of the 20th century. It was mainly due to the provisions of the Treaty of Rome according to which any decisions on common maritime transport had been postponed indefinitely. The Council Regulation No 141/62 was in force until the end of 1986. It excluded the maritime transport from the regulations concerning competition issues. The following sections of the article present both basic types of integration agreements between shipowners (especially those operating in container shipping) that were formed at the time described and the European Union changing attitude towards freedom of service provision in the maritime transport.